2008
DOI: 10.1016/j.jcin.2008.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Percutaneous Coronary Intervention With Bare-Metal and Drug-Eluting Stents for Cardiac Allograft Vasculopathy

Abstract: When compared with BMS, PCI with DES was safe and reduced the rate of angiographic restenosis in patients with CAV. A randomized clinical trial comparing BMS versus DES with longer follow-up is needed to identify the optimal long-term revascularization strategy in patients with CAV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 33 publications
1
42
0
2
Order By: Relevance
“…The optimal treatment for allograft vasculopathy in OHT patients is unknown, but PCI appears to be a therapeutic option. One of the main concerns of PCI in OHT patients is re-stenosis, as the allografted coronary vessel is in a proinflammatory state, which influences vessel remodeling (13)(14)(15)(16). Multivariate analysis revealed that in allograft vasculopathy, the use of stents decreased the risk of restenosis (odds ratio 0.34, p<0.05) compared with cutting balloon or other PCI methods (10,17).…”
Section: Discussionmentioning
confidence: 99%
“…The optimal treatment for allograft vasculopathy in OHT patients is unknown, but PCI appears to be a therapeutic option. One of the main concerns of PCI in OHT patients is re-stenosis, as the allografted coronary vessel is in a proinflammatory state, which influences vessel remodeling (13)(14)(15)(16). Multivariate analysis revealed that in allograft vasculopathy, the use of stents decreased the risk of restenosis (odds ratio 0.34, p<0.05) compared with cutting balloon or other PCI methods (10,17).…”
Section: Discussionmentioning
confidence: 99%
“…Ze względu na rozsiany charakter zmian w CAV w porównaniu z ogniskowymi zmianami miaż-dżycowymi rewaskularyzajca jest zabiegiem paliatywnym. Udowodniono przewagę stentów uwalniających lek (DES, drug-eluting stent) nad stentami metalowymi (BMS, bare metal stent) pod względem mniejszej liczby restenoz [29,30]. Mimo że pomostowanie aortalno-wieńcowe (CABG, coronary artery bypass grafting) nie jest metodą leczenia pierwszego rzutu u chorych z CAV, również z powodu rozległości zmian, istnieją dane wskazujące korzyści z jego zastosowania w wybranych grupach pacjentów.…”
Section: Leczenieunclassified
“…With the advent of drug eluting stents, preliminary studies suggest much lower restenosis rates. (Lee et al, 2008). PCI remains a palliative therapy, as CAV is a diffuse and progressive disease process.…”
Section: Prevention and Treatmentmentioning
confidence: 99%